THE STUDENTS’ PERCEPTION TOWARD THE IMPLEMENTATION GOOGLE MEET AS E-LEARNING PLATFORM AT THE SECOND-SEMESTER OF MADAKO UNIVERSITY - Theopilus C Motoh (Jurnal Madako Education, 2021)
The aimed of this research was to investigate the students’ perception toward the implementation Google meet as e-learning platform at the second-semester of Madako University. The design of this research was a qualitative research. The research samples were consisted of 16 students at B Class of 2th semester, which used purposive sampling. The data obtained from questionnaires and interviews. The technique used to analyze were percentage and Males and huberman. the data were analyzed through some steps among data reduction, data display and conclusion drawing. from the data analysis, the researcher found some conclusion of students’ perception was perceived of usefulness (14%), actual use (19%), perceived ease to use (36%), attitude aspect (6%), behavior intention (12.5%) and computer self-efficacy (50%). in the result of interview included perceived of usefulness, actual use, perceived ease to use,  attitude aspect, behavior intention and computer self-efficacy.Key words: Students’ Perceptions, Google Meet, Implementation, LMS